Biochemical diagnosis of wolman disease among clinically suspected patients - Marwa Bahaa Eldeen Abdellatif Dakroury; Ekram Maher Fateen; Mohammad Akmal Abdelrheem Elghor (Cairo : Marwa Bahaa Eldeen Abdellatif Dakroury, 2020)
Background: Lysosomal acid lipase (LAL) deficiency is an autosomal recessive disease, causing two different disorders, Wolman disease (WD) and Cholesteryl Ester Storage disease (CESD). WD is the severest type of lysosomal acid lipase deficiency. It causes accumulation of lipids in body organs and calcium deposits in the adrenal glands. The phenotype in infants include hepatosplenomegaly, failure to thrive, jaundice, vomiting, diarrhea, developmental delay, and anemia. It is life threatening in early childhood; however the late form appears after puberty and in some cases at older ages, leading to liver dysfunction. A recent method was established to measure the activity of the enzyme in a dried blood spot, using Lalistat 2 as an inhibitor.The aim was to diagnose Wolman disease among a group of high risk patients with organomegaly and establishing the dried blood spot technique. Subjects and methods: Eighty five subjects were recruited, 30 normal controls, 55 patients with severe hepatic congenital disorders. Four different enzyme activities were measured (Chitotriosidase, Bglucosidase, Sphingomylinase and Lysosomal acid lipase). Results: 55 patients were diagnosed : 17 Gaucher patients, 6 NiemannPick A/B patients, 3 Wolman patients and 29 patients were suspected to be other lysosomal storage disorder or NiemannPick C (NPC) patients for further investigations Conclusion: lasma chitotriosidase, peripheral leukocytic Ý-glucosidase and acid sphingomyelinase enzyme activity should be measured to all patients with clinical suspicion of WD, in order to exclude Gaucher disease (GD) and NiemannPick disease (NPD) as they share some symptoms on the early onset of the disease, and are of a higher risk to take place than Wolman. Screening for acid lipase enzyme activity is an accurate technique for the diagnosis of WD
Thesis (M.Sc.) - Cairo University - Faculty of Science - Department of Zoology
Issued also as CD
Keywords: Dried blood spot; Lysosomal acid lipase; Wolman disease